2018
DOI: 10.1590/1806-9061-2017-0499
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrated Sodium Calcium Aluminosilicate on Fatty Liver and the Composition of the Intestinal Microbiota in Overfed Landes Geese

Abstract: Goose fatty liver is a delicious food product and the overfeeding will cause the abnormal physiology of the geese. The objective of this study was to investigate the effect of supplementation with hydrated sodium calcium aluminosilicate (HSCAS) on the fatty liver, ileal and cecal microbiota of Landes geese during overfeeding. Sixty 70-day-old Landes geese (body weight= 3.0 ± 0.05 kg) were randomly divided into three groups, two of which were overfed with whole corn supplemented with or without HSCAS for 20 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The intestine is the place where the nutrients are digested and absorbed and also where the intestinal microbes are colonized. A study of Langdes Goose showed that the richness and diversity of the bacterial communities decreased in the ileum and cecum after overfeeding ( Tang et al., 2018 ). It was reported that the proliferation of C. perfringens eliminated the absorptive villi and resulted in the crypts between them to deepen, thus making the intestinal lining nonabsorptive, thick, and lumpy ( Zanu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intestine is the place where the nutrients are digested and absorbed and also where the intestinal microbes are colonized. A study of Langdes Goose showed that the richness and diversity of the bacterial communities decreased in the ileum and cecum after overfeeding ( Tang et al., 2018 ). It was reported that the proliferation of C. perfringens eliminated the absorptive villi and resulted in the crypts between them to deepen, thus making the intestinal lining nonabsorptive, thick, and lumpy ( Zanu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are rich resources, relatively inexpensive, and because of their structure can accumulate water, alkali cations, and substances regarded as toxic (Wang & Peng, 2010). The addition of aluminosilicates can prevent the growth of pathogens on animal farms (Ramos & Hernandez, 1997), which improves gastrointestinal health in birds (Tang et al, 2018) and their growth performance (Semenenko et al, 2020). All these aspects have a huge impact on the quality of produced poultry meat (Gálvez et al, 2020).…”
Section: Carcass Traits and Meat Qualitymentioning
confidence: 99%